The Synodal Church: A Path Towards Ennobling Women Religious - George, Bincy (Asian Horizons, 2024)
The path of synodality, with its emphasis on participation, communion and mission is a hope filled and grace filled endeavour. Women, in particular women religious, hope to have better opportunities to share their talents and potentialities in leadership roles and the ministry of the Church. The patriarchal influence of the ecclesiastical system made women and their contributions invisible in the past, and some supporters of the old tradition are still tempted to do so. The synodal Church opens up many areas of discrimination experienced by women and calls each member of the Catholic Church to transform this evil of exclusion with an attitudinal metanoia. It will surely bring about the praxis which ennobles women religious in particular and women in general. Sincere acknowledgement and appreciation will enhance women religious’ contributions rather than underestimating and exploiting them with the hierarchical power traditionally exercised in the Church.